2004
DOI: 10.1086/381227
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Abnormalities in Patients with Syphilis: Association with Clinical and Laboratory Features

Abstract: Serum RPR titer helps predict the likelihood of neurosyphilis. HIV-induced immune impairment may increase the risk of neurosyphilis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
327
6
57

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 432 publications
(414 citation statements)
references
References 23 publications
24
327
6
57
Order By: Relevance
“…12 There is also evidence that HIV infection may lead to more rapid progression to neurosyphilis. 13 It is therefore important to exclude HIV and syphilis in a patient presenting with neuropsychiatric disease and it is recommended that all patients diagnosed with syphilis be tested for HIV, and vice versa. 11,14,15 The National HIV Counselling and Testing Policy guidelines for diagnostic HIV testing support a sequential testing strategy, whereby HIV testing is initiated with a rapid screening test (finger prick).…”
Section: Introductionmentioning
confidence: 99%
“…12 There is also evidence that HIV infection may lead to more rapid progression to neurosyphilis. 13 It is therefore important to exclude HIV and syphilis in a patient presenting with neuropsychiatric disease and it is recommended that all patients diagnosed with syphilis be tested for HIV, and vice versa. 11,14,15 The National HIV Counselling and Testing Policy guidelines for diagnostic HIV testing support a sequential testing strategy, whereby HIV testing is initiated with a rapid screening test (finger prick).…”
Section: Introductionmentioning
confidence: 99%
“…Its moderate sensitivity (30-70%) in immunocompetent patients 4 and its significantly decreased sensitivity in patients who are immunosuppressed due to HIV, makes it necessary to use other techniques for diagnosing this condition. These may include cellularity and CSF protein levels, in those cases that cannot be detected through VDRL 5,6,7 . High cellularity and CSF protein levels are indicative criteria of neurosyphilis in the absence of other diseases.…”
mentioning
confidence: 99%
“…Numerous prior studies have shown that the risk of neurosyphilis in HIV-infected patients with systemic syphilis is significantly higher in the setting of neurological symptoms such as headache or ocular symptoms. 24,30,31 Additionally, reduced peripheral blood CD4+ T-cell count has been associated with the risk of neurosyphilis: CD4 T-cell counts of 350 uL -1 in several studies 24,31,32 and 500 uL -1 in a more recent study 30 have been clearly associated with an increased probability of neurosyphilis in HIV-infected persons, as defined by CSF criteria. Some controversy remains as to whether high serum rapid plasma reagin (RPR) titres also predict neurosyphilis.…”
Section: Laboratory Definitions Of Neurosyphilismentioning
confidence: 99%
“…Given this, most recent definitions have used a cut-off of >20 WBCs/uL as diagnostic of neurosyphilis in HIV-infected individuals who have a positive blood syphilis titre but a non-reactive CSF-VDRL, as employed in a large prospective study of syphilis in HIV-infected patients. 24 Others have used a lower cut-off, 25 which may be most appropriate in HIV patients with a low peripheral blood CD4+ T-cell concentration, who are taking combination ART or who have undetectable plasma HIV RNA, because these lower the risk of HIV-related CSF pleocytosis. 23,26 Other tests not currently used clinically that may contribute to the diagnosis of asymptomatic neurosyphilis include: (i) the proportion of CSF lymphocytes that are B-cells; 27 and (ii) the CSF concentration of the chemokine C-X-C motif ligand 13 (CXCL-13), a B-cell chemoattractant.…”
Section: Laboratory Definitions Of Neurosyphilismentioning
confidence: 99%